Long-term survival after endoscopic resection versus surgery in early gastric cancers - Kim, Young-Il; Kim, Young-Woo; Choi, Il Ju; Kim, Chan Gyoo; Lee, Jong Yeul; Cho, Soo-Jeong; Eom, Bang Wool; Yoon, Hong Man; Ryu, Keun Won; Kook, Myeong-Cheorl (Endoscopy, 2015)
Background and study aim: Endoscopic resection for early gastric cancers that meet the expanded indication is considered to be an investigational treatment. The study aim was to evaluate long-term outcomes of endoscopic resection compared with surgery for early gastric cancers meeting the expanded indication. Methods: We retrospectively reviewed data from patients who underwent endoscopic resection or surgery for gastric cancers meeting the expanded indication between 2001 and 2009. Overall survival rate was the primary outcome; gastric cancer recurrence rates and complication rates were secondary outcomes.Results: Among 457 patients included, 165 underwent endoscopic resection and 292 surgery, with median follow-up duration of 58.6 months. The 5-year overall survival rates were 97.5 % and 97.0 % for endoscopic resection and surgery, respectively; Kaplan–Meier analysis showed no significant difference (P = 0.425). The 5-year gastric cancer recurrence rate was higher for endoscopic resection than for surgery (4.8 % vs. 0.3 %; P < 0.001) mainly because of metachronous cancers which developed only in the endoscopic resection group (9/165, 5.5 %). Most of the metachronous cancers (88.9 %) were curatively treated with endoscopic resection. Early complication rates were similar between the groups (P = 0.557), but the endoscopic resection group had more grade III or higher complications according to the Clavien–Dindo classification compared with the surgery group (4.8 % vs. 1.4 %, P = 0.026). Late complications occurred only following surgery (4.8 %, P = 0.004), and most (92.9 %) were grade III or higher. Conclusions: Endoscopic resection may be an optimal alternative to surgery for gastric cancers that meet the expanded indication criteria, because of a comparable long-term overall survival rate.